The Readiness of PT Semen Indonesia (Persero) Tbk facing carbon tax policy implementation plans - Praditya Rizky; Titi M Putranti (Institute of Computer Science (IOCS), 2023)
The research paper discusses the government's plan to implement a carbon tax in Indonesia to promote sustainable economic and business activities, with the goal of addressing environmental preservation and climate crisis impact reduction. The carbon tax is designed to tax economic activities that produce excessive carbon emissions and other negative environmental impacts. The paper also considers the role of the economic sector in supporting sustainable social and environmental development and discusses Indonesia's commitment to the 2015 Paris Agreement. The implementation of the carbon tax aims to reduce emissions, generate state revenue, and facilitate the development of new renewable energy. It also addresses the readiness of PT Semen Indonesia (Persero) Tbk regarding the implementation of the carbon tax, focusing on communication, resources, disposition, and bureaucratic structure. The paper recommends strategies for successfully overcoming challenges associated with carbon tax implementation. Overall, it provides insights into the potential impact and readiness of PT Semen Indonesia (Persero) Tbk in implementing the carbon tax policy in Indonesia.